Resposta:
[tex]\textsf{Leia abaixo}[/tex]
Explicação passo-a-passo:
[tex]\mathsf{h(x) = (0,5)^{x - 2}}[/tex]
[tex]\mathsf{y = (0,5)^{x - 2}}[/tex]
[tex]\mathsf{x = (0,5)^{y - 2}}[/tex]
[tex]\mathsf{log\:x = log\:(0,5)^{y - 2}}[/tex]
[tex]\mathsf{log\:x = (y - 2)\:log\:0,5}[/tex]
[tex]\mathsf{y - 2 = \dfrac{log\:x}{log\:0,5}}[/tex]
[tex]\mathsf{y = \dfrac{log\:x}{log\:0,5} + 2}[/tex]
[tex]\mathsf{y =\dfrac{log_{\:0,5}\:(x)}{log_{\:0,5}\:0,5}+ 2}[/tex]
[tex]\mathsf{y =\dfrac{log_{\:0,5}\:x}{1}+ 2}[/tex]
[tex]\boxed{\boxed{\mathsf{h^{-1}(x) = 2 + log_{\:0,5}\:(x)}}}\leftarrow\textsf{letra B}[/tex]